2019
DOI: 10.1186/s12872-019-1168-2
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term effectiveness and safety of self-management of oral anticoagulants in real-world settings

Abstract: Background The patient self-management (PSM) is an effective approach for controlling the international normalized ratio, INR, within the therapeutic range. Nevertheless, most of the literature derives from randomized clinical trials, and no from routine clinical practice. The main objective of the present study was to evaluate long-term effectiveness and safety of PSM of oral anticoagulants (OACs) in real-world settings. Methods This prospective cohort study involved 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Despite the advantages of PSM, the estimated acceptance and implementation rate of PSM in the United States is well below 1% 9 . Conversely, PSM is more common in European countries 10–13 . In one survey, 8.5% of family practice patients receiving vitamin K antagonist therapy in Germany were using PSM 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the advantages of PSM, the estimated acceptance and implementation rate of PSM in the United States is well below 1% 9 . Conversely, PSM is more common in European countries 10–13 . In one survey, 8.5% of family practice patients receiving vitamin K antagonist therapy in Germany were using PSM 14 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Conversely, PSM is more common in European countries. [10][11][12][13] In one survey, 8.5% of family practice patients receiving vitamin K antagonist therapy in Germany were using PSM. 14 A long-term nationwide cohort study in Swiss patients indicated that PSM was used for a variety of indications including venous thromboembolism (40.6%), prosthetic heart valves (32.0%), and atrial fibrillation (17.8%).…”
Section: Introductionmentioning
confidence: 99%
“…Development of point-of-care (POC) INR determination by bedside real-time portable coagulometers has revolutionized management of warfarin anticoagulant therapy, allowing patients to self-test and self-manage their anticoagulant therapy conveniently. In recent years, the popularization and rapid development of the Internet have provided new opportunities for clinical anticoagulation monitoring and post-discharge follow-up ( 12 14 ). In this review, we summarize the latest research on warfarin anticoagulant therapy that takes advantage of new developments in Internet technology and self-testing.…”
Section: Introductionmentioning
confidence: 99%
“…After publication of the original article [1], we were notified that the name of the software mentioned in the Background section is TAONET and not Tao Net.…”
mentioning
confidence: 99%